The Influence of Nationalism on The Fulfillment of Tax Obligations is Moderated Knowledge of MSMES Within National Universities - Agil Syahrial; Muhammad Nur; Kumba Digdowiseiso (Jurnal Syntax Transformation, 2024)
This study aims to determine the effect of Sense of Nationalism on the Fulfillment of Tax Obligations with Knowledge as a Moderating Variable. This study uses primary data obtained from respondents' answers to the questionnaire used in the study. The sample of this study amounted to 100 MSME actors in the National University. The sampling technique used was convenience sampling. The data analysis method used Descriptive Statistics, Data Quality Test, Classical Assumption Test, and Hypothesis Testing which consisted of Simple Regression Analysis Method, and Moderated Regression Analysis (MRA) Method, F Test, Coefficient of Determination, and T Test. The results showed that the effect of The sense of Nationalism has a positive and significant effect on the fulfillment of tax obligations. Knowledge has a significant and negative effect on the relationship between Sense of Nationalism and Fulfillment of Tax Obligations.